Progress and perspectives for microbial production of farnesene. (March 2022) - Liu, Yinghang; Wang, Zhaoxuan; Cui, Zhiyong; Qi, Qingsheng; Hou, Jin
Highlights: Metabolic engineering strategies for improving farnesene biosynthesis are summarized. Emerging tools and methods for further improving farnesene production are proposed. Production of farnesene from cheap or waste feedstock is emphatically introduced. The new synthetic pathways could be applied to farnesene biosynthesis. The perspectives for future farnesene biosynthesis are discussed. Abstract: Farnesene is increasingly used in industry, agriculture, and other fields due to its unique and excellent properties, necessitating its efficient synthesis. Microbial synthesis is an ideal farnesene production method. Recently, researchers have used several strategies to optimize the production performance of microorganisms. This review summarized these strategies, including regulation of farnesene synthesis pathways, and proposed some emerging tools and methods in stain engineering. Meanwhile, new farnesene biosynthetic pathways and effective farnesene production from cheap or waste substrates were emphatically introduced. Finally, future farnesene biosynthesis challenges were discussed.